O‘ZBEK TILIDA REKLAMALARNING SINTAKTIK STRUKTURASI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The article deals with the syntactic construction of advertising texts. The main task of the advertising text is to attract attention to a specific product, product, thing or event through a relatively short message. The brevity and meaningfulness of noun phrases are suitable for fulfilling this task, which leads to their frequent use in advertising texts.
Keywords: advertising texts, syntactic structure, sentence structure of advertisements, noun phrases.